Glucosinolate extract from radish (Raphanus sativus L.) seed attenuates high-fat diet-induced obesity: insights into gut microbiota and fecal metabolites - Zhu, Quanfeng; Zhang, Peng; Liu, Daqun; Tang, Leilei; Yu, Jiawen; Zhang, Chengcheng; Jiang, Guojun (Frontiers in Nutrition, 2024)
Background: Radish seed is a functional food with many beneficial health effects. Glucosinolates are characteristic components in radish seed that can be transformed into bioactive isothiocyanates by gut microbiota. Objective: The present study aims to assess anti-obesity efficacy of radish seed glucosinolates (RSGs) and explored the underlying mechanisms with a focus on gut microbiota and fecal metabolome. Methods: High-fat diet-induced obese mice were supplemented with different doses of RSGs extract for 8 weeks. Changes in body weight, serum lipid, alanine aminotransferase (ALT), and aspartate aminotransferase (AST) levels; and pathological changes in the liver and adipose tissue were examined. Fecal metabolome and 16S rRNA gene sequencing were used to analyze alterations in fecal metabolite abundance and the gut microbiota, respectively. Results and Conclusion: Results showed that RSG extract prevented weight gain and decreased serum lipid, ALT, AST levels and lipid deposition in liver and epididymal adipocytes in obese mice. Treatment with RSG extract also increased gut microbiota diversity and altered the dominant bacteria genera in the gut microbiota, decreasing the abundance of Faecalibaculum and increasing the abundance of Allobaculum, Romboutsia, Turicibacter, and Akkermansia. Fecal metabolome results identified 570 differentially abundant metabolites, of which glucosinolate degradation products, such as sulforaphene and 7-methylsulfinylheptyl isothiocyanate, were significantly upregulated after RSG extract intervention. Furthermore, enrichment analysis of metabolic pathways showed that the anti-obesity effects of RSG extract may be mediated by alterations in bile secretion, fat digestion and absorption, and biosynthesis of plant secondary metabolites. Overall, RSG extract can inhibit the development of obesity, and the obesity-alleviating effects of RSG are related to alternative regulation of the gut microbiota and glucosinolate metabolites.